Kemenangan Ideologis dan Kekalahan Politik Wacana Politik Etnis Minang dalam Pemilihan Presiden 2014 dan 2019 - Khusairi, Abdullah; Nasir, Muhammad; Fata, Ahmad Khoirul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
This article examines the political discourse of the Minang ethnic group in the Presidential Elections (Pilpres) of 2014 and 2019. In both elections, the Minang candidates did not win nationally but achieved a landslide victory in the West Sumatra province. This has created a stigma for the Minang ethnic group as one with a strong political identity and a province with a hardline stance. This study aims to understand the political discourse of the Minang ethnic group in choosing national leaders. The study employs Norman Fairclough's Critical Discourse Analysis approach, which identifies four interconnected dimensions: linguistic, discursive, social, and ideological. This research is a qualitative study using critical analysis methods. Data was collected through in-depth interviews with Minang figures (traditional leaders, religious figures, politicians, academics, and cultural figures). The findings indicate that the political communication of the Minang ethnic group did not undergo a shift in perspective when it comes to viewing leadership issues. For the Minang ethnic group, a leader is highly regarded and given priority. Leaders must possess the qualities of